This is somehow related to this problem but I don't have any idea about it.

Let $a$, $b$, $c$ and $d$ be positive reals such that $a+b+c+d=4$. Prove that: $$\frac{1}{a+3}+\frac{1}{b+3}+\frac{1}{c+3}+\frac{1}{d+3}\le \frac{1}{abcd}$$

Now I also tried to prove the $3$ variable version : $$\frac{1}{a+2}+\frac{1}{b+2}+\frac{1}{c+2}\le \frac{1}{abc}$$ where $a,b,c>0$ with $a+b+c=3$. But I haven't been able to solve it too. Anyone can help?? Thanks a lot.


$\sum$ will be used to denote the cyclic sum.

For the second inequality, let $t=ab+bc+ca$. Note that $t\le 3$, and also: $$3t=(a+b+c)(ab+bc+ca)\ge 9\sqrt[3]{(abc)(a^2b^2c^2)}=9abc$$ Now, by Cauchy-Schwarz: $$\sum\frac{2bc}{a+2}=2\sum\frac{(bc)^2}{abc+2bc}\ge \frac{2t^2}{3abc+2t}\ge \frac{2t}{3}$$ Note further that $\frac{2t}{3}-(t-1)=\frac{3-t}{3}\ge 0$ since $t\le 3$. Hence: $$\sum\frac{2bc}{a+2}\ge ab+bc+ca-1\implies \sum (bc-\frac{2bc}{a+2})\le 1\implies \sum\frac{1}{a+2}\le\frac{1}{abc}$$ as desired.

A similar trick works for the first inequality. Let $t=abc+bcd+cda+dab$ this time. Then by repeated applications of AM-GM, $$t=ab(c+d)+cd(a+b)\le (\frac{a+b}{2})^2(c+d)+(a+b)(\frac{c+d}{2})^2=\frac{(a+b+c+d)^2}{4}=4$$ Also, note that by AM-GM: $$4t=(a+b+c+d)(abc+bcd+cda+dab)\ge 16\sqrt[4]{(abcd)(a^3b^3c^3d^3)}=16abcd$$ Using these estimations: $$\sum \frac{3bcd}{a+3}=3\sum\frac{(bcd)^2}{abcd+3bcd}\ge \frac{3t^2}{4abcd+3t}\ge\frac{3t}{4}$$ And $\frac{3t}{4}-(t-1)=\frac{4-t}{4}\ge 0$, so that: $$\sum\frac{3bcd}{a+3}\ge abc+bcd+cda+dab-1\implies \sum (bcd-\frac{3bcd}{a+3})\le 1\implies \sum\frac{1}{a+3}\le \frac{1}{abcd}$$ as desired.

Note: Using this same method, the $n$-variable inequality can also be proven.


We will prove a stronger inequality: If $a_1, a_2, \cdots, a_n$ are $k$ positive number such that $$\sum^{n}_{i=1}a_i = n$$ Then

$$\sum^{n}_{i=1} \dfrac{1}{a_i+n-1} \leq 1, \forall n \in \mathbb{N}$$

The above inequality is equivalent to

$$ \sum^{n}_{i=1} \Bigg( \dfrac{1}{n-1} - \dfrac{1}{a_i+n-1} \Bigg) \geq \dfrac{1}{n-1} $$ $$ \Leftrightarrow \sum^{n}_{i=1} \dfrac{a_i}{a_i + n - 1} \geq 1$$

Applying Schwarz inequality, we have $$ LHS = \sum^{n}_{i=1} \dfrac{(\sqrt{a_i})^2}{a_i+n-1} = P$$

It suffices to show that $$P \geq 1 \Leftrightarrow (\sum^{n}_{i=1}a_i)^2 \geq \sum^{n}_{i=1}a_i + n(n-1)$$ $$ \Leftrightarrow 2\sum_{1\leq i < j \leq n}\sqrt{a_ia_j} \geq n(n-1)$$

By applying AM-GM inequality for $\dfrac{n(n-1)}{2}$ numbers on the LHS, the conclusion follows.

P/S: This idea belongs to my Math teacher. He is very good at inequalities.

  • $\begingroup$ If $\sum_{i=1}^na_i=n$, then in fact $$n^2\sum\frac{1}{a_i+n-1}=(\sum (a_i+n-1))(\sum\frac{1}{a_i+n-1})\ge n^2$$ by Cauchy-Schwarz, so $\sum\frac{1}{a_i+n-1}\ge 1$. $\endgroup$ – Apple Jul 23 '14 at 18:17
  • $\begingroup$ Wow that was much faster :) I checked my note and the condition in my problem is $a_1a_2\cdots a_n = n$. I think it's a good way to strengthen the inequality :) $\endgroup$ – primitiveroot Jul 23 '14 at 18:27

Let $a+b+c+d=4u$ and $ab+ac+ad+bc+bd+cd=6v^2$.

Hence, by AM-GM $abcd\leq v^4$ and by C-S $$\frac{1}{abcd}-\sum_{cyc}\frac{1}{a+3}=\frac{1}{abcd}-\frac{4}{3}-\sum_{cyc}\left(\frac{1}{a+3}-\frac{1}{3}\right)=$$ $$=\frac{1}{abcd}-\frac{4}{3}+\sum_{cyc}\frac{a}{3(a+3)}\geq\frac{1}{abcd}-\frac{4}{3}+\frac{(a+b+c+d)^2}{3\sum\limits_{cyc}(a^2+3)}=$$ $$=\frac{1}{abcd}-\frac{4}{3}+\frac{16}{3\sum\limits_{cyc}(a^2+3)}=\frac{u^2}{abcd}-\frac{4}{3u^2}+\frac{16}{3(16u^2-12v^2+12u^2)}\geq$$ $$\geq\frac{u^2}{v^4}-\frac{4}{3u^2}+\frac{4}{3(7u^2-3v^2)}\geq0,$$ where the last inequality it's $$(u^2-v^2)(7u^4+4u^2v^2-4v^4)\geq0,$$ which is true because $u^2\geq v^2$.



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.